Limitations of the Right to a Healthy Environmentin the Forest Legislation - Elena N. Abanina (Сибирское юридическое обозрение, 2017)
The article investigates individual cases of limitation of the right to stay in the forest by regulations of forest legislation. The cases of restricting the stay of citizens in the forests in order to ensure fire safety and sanitary security in forests and the safety of citizens in the performance of work are analyzed. Judgments of the courts on the legality and illegality of the fencing of forest areas that prevent citizens from accessing them are given. Attention is drawn to the practical problems arising from the imperfection of legal regulation of relations in this area.